Evidence-based Positron Emission Tomography: Summary of Recent Meta-analyses on PET - Treglia, Giorgio; Giovanella, Luca (Springer Nature, 2020)
This open access book summarizes the findings of recent evidence-based articles (meta-analyses) on the use of positron emission tomography (PET) for various clinical indications. It is divided into five main sections, starting with an introduction to PET and meta-analysis. In turn, the second part addresses evidence-based PET in oncology, providing a broad overview of its use for different types of tumours. The remaining sections are focused on the use of PET in cardiology, in infectious and inflammatory diseases, and in neurology, respectively. Given its scope and the wealth of information it provides, the book will be an invaluable tool for clinicians with various specialties, as well as international scientific societies interested to the recent evidence-based data about PET.